Pengaruh Orientasi Kewirausahaan, Kapasitas Daya Serap Dan Strategi Inovasi Terhadap Keunggulan Bersaing (Studi Pada Ikm Pakaian Jadi Di Kota Sukabumi) - Nabila Salsabila Rahman; Erry Sunarya; Dicky Jhoansyah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine the effect of entrepreneurial orientation, absorptive capacity, and innovation strategy on competitive advantage using quantitative methods through descriptive and associative approaches. The sample used in this study was 46 apparel SMIs business actors in Sukabumi City using non probability sampling saturated sample method. This study used multiple lienar regression as a data analysis technique. The results in this study indicate that entrepreneurial orientation, absorptive capacity and innovation strategy simultaneously affecr competitive advantage. While in the results of hypothesis testing entrepreneurial orientation has no partial effect on competitive advantage, however, absorptive capacity and innovation strategy have a partially significant effect on competitive advantage.